1856 Cleveland Gen. Ordinances 128, An Ordinance to establish a magazine and regulate the sale of powder, § 3 (1856) - (:unkn) unknown (General Publisher, 1856)
No person shall keep within the city, any quantity of gunpowder exceeding twenty-five pounds, or of gun cotton exceeding five pounds, for a longer period than twenty-four hours, except in the powder magazine; and said twenty-five pounds shall be kept in tin or copper canisters, neither of which shall contain over seven pounds and shall be labelled “gunpowder,” and be kept near the front or rear entrance of every building in which it is contained."
--
Keywords: GUN POWDER STORAGE